Evaluation of risk assessment scales for decubitus ulcer in intensive care patients - Simone Pereira Machado; Selma R de Castilho; Beatriz GRB Oliveira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This study is about the effectiveness of the scales of Braden and Cubbin & Jackson in patients of intensive therapy. The objectives were to apply the scales, to compare sensibility and specificity and to discuss their application as a preventive strategy to minimize the development of ulcers. It is a prospective, quantitative research, which was accomplished in three units of intensive therapy. The collection of the data was made with 39 patients in the period of June to August of 2005, with which we used formularies and the scales mentioned previously. The data were stored in spreadsheet of Microsoft Excel, with which the sensibility and the specificity of the 2 scales were calculated and contingency tables were mounted, as well positive and negative preditive values. The results point that the two scales presented good sensibility, with the scale of Braden being more sensitive (0,93) than the Cubbin & Jackson's (0,75). On the other hand, the scale of Cubbin & Jackson showed a larger specificity (0,83) than the Braden's one (0,47). If we consider the two factors, the scale of Cubbin & Jackson is shown to be more appropriate to the patients of ICU because the sum of its sensibility and specificity is 1,58 against 1,40 for the scale of Braden. We concluded that the two scales have shown to be effective, and Cubbin & Jackson's is more suitable, once it is more specific and presents less false-positive cases. The present study will contribute to the planning of caring with the patient in a critical stage of sickness, with committed mobility and in risk of pressure ulcer, resulting in the implementation of fast and effective actions for its prevention.